2015
DOI: 10.1159/000367658
|View full text |Cite
|
Sign up to set email alerts
|

Total Laparoscopic Hysterectomy in Obese and Morbidly Obese Women

Abstract: Background: The study aimed at estimating the effect of body mass index (BMI), used to classify non-obese, obese, and morbidly obese patients, on clinical outcomes in total laparoscopic hysterectomy (TLH) cases. Methods: This retrospective cohort study included 153 patients who underwent TLH for benign, premalignant, or malignant conditions between August 2010 and June 2013. Patients were divided into 3 groups according to BMI, and the following variables were analyzed: operation time, conversion rate, blood l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
(49 reference statements)
0
9
0
1
Order By: Relevance
“…Similarly, average days of postopera ve hospital stay in obese pa ents a er 15 TLH was one day , ranging from 1-5 days. In another study by Otake A et al (2019), mean postopera ve hospital stay was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) days in normal BMI group, 5 (4-10) days in 3 overweight group and 5 (4-37 ) days in obese group. In our study, mean postopera ve hospital stay was 3.46±0.68 days (range: 3-6 days) in high BMI group and 3.05±0.47 days (range:3-4days), the difference was sta s cally not significant (p=0-74 Chopin N et al (2009) analyzed 1460 women who underwent TLH among which 1021(69.9%) had normal BMI, 338 (23.2%) were overweight pa ents and 101 (6.9%) were obese (BMI >30).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, average days of postopera ve hospital stay in obese pa ents a er 15 TLH was one day , ranging from 1-5 days. In another study by Otake A et al (2019), mean postopera ve hospital stay was 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) days in normal BMI group, 5 (4-10) days in 3 overweight group and 5 (4-37 ) days in obese group. In our study, mean postopera ve hospital stay was 3.46±0.68 days (range: 3-6 days) in high BMI group and 3.05±0.47 days (range:3-4days), the difference was sta s cally not significant (p=0-74 Chopin N et al (2009) analyzed 1460 women who underwent TLH among which 1021(69.9%) had normal BMI, 338 (23.2%) were overweight pa ents and 101 (6.9%) were obese (BMI >30).…”
Section: Discussionmentioning
confidence: 91%
“…The difference was sta s cally not significant (p0.185). Guraslan H et al(2015) reported the mean opera on me significantly higher in obese (128 ± 32 min) and morbidly obese pa ents (130 ± 21 min) than in non-obese (110 ± 23 min) pa ents. The most important reason for this difference is the restricted movement of the laparoscopic instruments Similarly, in the study by Bardens D et al, mean opera ve me was 129.0±58.6 minutes in normal weight group (n=90), 135.4±46.9 minutes in overweight group (n=47) and 154±64.2 minutes in obese women with BMI >30 (n=52).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Güraslan et al [7] found no difference in hemoglobin changes in patients with normal BMI, obese, and morbidly obese patients undergoing a total laparoscopic hysterectomy 1.11 ± 1.5 g/dL, 1.15 ± 1.7 g/dL, 1.11 ± 1.8 g/dL (p = 0.427), respectively. They recommended TLH as a safe and viable alternative to abdominal hysterectomy in obese and morbidly obese patients.…”
Section: Discussionmentioning
confidence: 96%
“…Bizim çalışmamızda uzun operasyon süresi ve yüksek laparotomiye dönme oranlarının nede-ni TLH grubundaki hastaların ortalama vücut kitle indeksinin obezite sınırının üstünde olması olabilir (Ortalama VKİ 32 ± 6). Daha önce içinde bizim çalışmamızında bulunduğu bir çok çalışmada obezitenin uzun operasyon süresi ve artmış laparotomiye dönme oranlarıyla ilişkili olduğu rapor edilmiştir [20,22,23]. Laparoskopik yaklaşımın en önemli avantajlarından bir tanesi abdominal yaklaşıma göre hızlı iyileşme ve artmış yaşam kalitesidir.…”
Section: Discussionunclassified